The role of SALL1-MGST1 axis-mediated ferroptosis inhibition in chemoresistance of retinoblastoma - Zhuang Xiong; Weiwei Zhang; Xuebing Yu; Ruoshu Gu; Xue Zhang (PLoS ONE, 2026)
Retinoblastoma (RB) is the most prevalent intraocular malignant tumor in infants and young children, predominantly driven by the biallelic inactivation of the RB1 gene. Although multimodal treatment strategies have markedly improved the survival rates of pediatric patients, chemotherapy resistance, particularly carboplatin (CBP) resistance, remains a major clinical hurdle. In recent years, ferroptosis, an iron-dependent and lipid peroxide-driven form of programmed cell death, has garnered significant attention for its role in tumor drug resistance. This study investigates the functional mechanisms of the transcription factor Spalt-Like Transcription Factor 1 (SALL1) and its downstream target gene Microsomal Glutathione S-Transferase 1 (MGST1) in RB. Bioinformatics analysis revealed a significant upregulation of SALL1 in RB, accompanied by enhanced activity of its regulatory network. Experimental evidence from ChIP-qPCR and luciferase reporter assays indicated that SALL1 binds to the promoter region of MGST1 and enhances its promoter transcriptional output. Functionally, knockdown of SALL1 suppressed cell proliferation and induced ferroptosis, as evidenced by increased levels of lipid peroxidation, elevated malondialdehyde (MDA), and decreased glutathione (GSH) levels. These effects were reversible by the ferroptosis inhibitor Fer-1 or overexpression of MGST1. In the CBP-resistant cell line Y79-R, knockdown of SALL1 notably reduced the IC50, enhanced chemosensitivity, and promoted cell death, a phenotype that could be rescued by overexpression of MGST1. Mechanistically, the SALL1-MGST1 axis promotes RB cell survival and drug resistance by inhibiting lipid peroxidation and ferroptosis. This study is the first to elucidate that the SALL1-MGST1 axis mediates CBP resistance in RB through the regulation of ferroptosis, providing a novel therapeutic target for reversing drug resistance.